Blessed Are the Peacemakers : Small Histories During World War II, Letter Writing, and Family History Methodology. - Rumsey, Suzanne Kesler, 1977- (University of Alabama Press, 2021)
"An uncommon and intimate account of the lives of two conscientious objectors"-- Provided by publisher.
Description based upon print version of record.
Keywords: Kesler, Benjamin Elias, -- Jr., -- 1920-1981.; Kesler, Miriam Elizabeth, -- 1925-2013.; Civilian Public Service -- Biography.; Dunkard Brethren -- Biography.; Civilian Public Service; Dunkard Brethren; World War, 1939-1945 -- Conscientious objectors -- United States -- Biography.; Conscientious objectors -- United States -- Biography.; Pacifists -- United States -- Biography.; Married people -- United States -- Correspondence.; Letter writing -- United States.; Genealogy -- Authorship.; Guerre mondiale, 1939-1945 -- Objecteurs de conscience -- États-Unis -- Biographies.; Objecteurs de conscience -- États-Unis -- Biographies.; Pacifistes -- États-Unis -- Biographies.; Couples mariés -- États-Unis -- Correspondance.; Social Activists.; BIOGRAPHY & AUTOBIOGRAPHY.; World War II.; Military.; HISTORY.; 20th Century.; United States.; Composition & Creative Writing.; Letters.; LITERARY COLLECTIONS.; Conscientious objectors; Genealogy -- Authorship; Letter writing; Married people; Pacifists; United States; 1939-1945; e-books.; Biographies; Personal correspondence; Livres numériques.